The effectiveness of blended learning with combined synchronized and unsynchronized settings on self-efficacy and learning achievement - I Dewa Ayu Made Budhyani; Made Candiasa; Made Sutajaya; Putu Kerti Nitiasih (International Journal of Evaluation and Research in Education (IJERE), 2022)
This study analyzed the effect of blended learning with combined synchronized and unsynchronized settings on self-efficacy and achievement of the students in learning basic design. The population was 145 students of vocational schools (sekolah menengah kejuruan/SMK) who learned basic design. The schools were selected through multistage random sampling which selected four schools with 115 students. The data for self-efficacy were collected with a questionnaire and those for learning achievement with a multiple-choice test. The data were analyzed using descriptive statistical test and inferential statistical test of multivariate analysis of variance (MANOVA). The study found that blended learning with combined synchronized and unsynchronized settings has a positive effect on the students’ self-efficacy and learning achievement in basic design, thus making the learning more joyful and more conducive.